South Africa Immigration Debate: Public Perceptions And Contributing Factors to Crime - Magadze, Tshimangadzo Oscar (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2026)
This study investigates public perceptions of illegal immigration in South Africa. It particularly focuses on the perceived relationship between immigration and crime rates. Despite limited empirical evidence linking immigration to increased crime, public discourse conflates undocumented immigration with criminal activity. This prompted policy debates including the current review of South Africa’s Immigration Amendment Bill. Guided by Intergroup Threat Theory, this research examines how realistic threats (concerns over tangible resources and safety) and symbolic threats (concerns over cultural identity) shape public attitudes. A quantitative cross-sectional survey was conducted with 131 South African residents using convenience sampling. Data were analyzed through descriptive statistics in SPSS 29.0. Findings reveal an overwhelming consensus (96.3%) that immigration worsens crime, which is primarily attributed to undocumented status facilitating criminal activity (88.5%). Notably, 46.6% believe immigrants come to benefit from social services rather than provide for families (35.1%), and 78.8% believe controlled migration would reduce crime. Paradoxically, 64.9% express willingness to develop relationships with immigrants despite negative perceptions. The study concludes that public perceptions of immigration as a crime driver have become nearly widespread in South Africa, which creates a significant gap between public belief and empirical evidence. This disconnect highlights the urgent need for transparent communication from authorities about immigration realities and addressing underlying socioeconomic anxieties that fuel these perceptions, rather than treating immigration solely as a crime issue.